Katie and the Mustang. Book three - Duey, Kathleen (New York, N.Y., U.S.A. : Puffin Books, 2004)
Katie continues the journey west with the Kyler family and a traveling circus joins the caravan, but when she reaches Fort Laramie she is disappointed to learn her letter never reached her Uncle Jack.
008-012.
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Orphans -- Fiction; Horses -- Fiction; Wild horses -- Fiction; Frontier and pioneer life -- Fiction